2012
DOI: 10.1111/j.2040-1124.2012.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial impairment and bone marrow‐derived CD34+/133+ cells in diabetic patients with erectile dysfunction

Abstract: Aims/Introduction: The present study was undertaken to determine vascular endothelial impairment and endothelial progenitor cells (EPCs) in patients with type 2 diabetes mellitus and erectile dysfunction (ED). Materials and Methods: A total of 100 type 2 diabetic men were enrolled. Flow-mediated dilatation (FMD) and anaerobic threshold (AT) were measured. Also, EPCs in the peripheral blood were determined by flow cytometry. Results: In the 42 ED diabetic patients, FMD and AT were significantly less than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…In fact, contradictory findings have been reported in what regards cEPCs in diabetes. Several studies have presented a decrease in vascular progenitors in diabetic PB [Murata et al, ; Saito et al, ; Westerweel et al, ; Maiorino et al, ], whereas, others have shown an increase in these cell populations [Fadini et al, ; Liu et al, ; Flammer et al, ]. This relates to the so‐called diabetic angiogenic paradox [Costa, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, contradictory findings have been reported in what regards cEPCs in diabetes. Several studies have presented a decrease in vascular progenitors in diabetic PB [Murata et al, ; Saito et al, ; Westerweel et al, ; Maiorino et al, ], whereas, others have shown an increase in these cell populations [Fadini et al, ; Liu et al, ; Flammer et al, ]. This relates to the so‐called diabetic angiogenic paradox [Costa, ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that a good glycemic control, besides improving endothelial function and reducing oxidative markers [Fadini et al, ], and may also increase circulating EPCs (cEPCs) [Hortenhuber et al, ]. Several reports demonstrated a decrease in cEPCs levels in ED patients with cardiovascular risk factors, including diabetes [Murata et al, ; Maiorino et al, ]. A recent study, has showed a reduction of cEPCs in type 1 diabetics (T1D) with ED, which correlated with EDys and testosterone levels [Maiorino et al, ].…”
mentioning
confidence: 99%
“…FMD of the right brachial artery was determined by one investigator (AA) between 16:00 and 18:00 hours after a 15-minute rest, using a 12-MHz ultrasound instrument (UNEXEF18G, UNEX Corp., Nagoya, Japan), as previously described [17]. The brachial artery was imaged in the longitudinal section just above the antecubital fossa and internal diameters from the anterior to posterior intimal interfaces were measured at end-diastole using B-mode imaging as baseline.…”
Section: Methodsmentioning
confidence: 99%
“…In all, 15 studies examined endothelial dysfunction as an outcome, with all these measuring FMD and none measuring RHI. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Twelve studies examined cIMT outcomes, 28,34,35,38,40,[42][43][44][45][46][47][48] five studies measured CAC 28,29,37,49,50 and six studies had various measures of vascular stiffness and peripheral vascular disease such as PWV, Augmentation Index (AIx), ABI, and TBI. 28,[51][52][53][54][55] All the studies with FMD (n=15) and cIMT (n=12) outcomes were included in the meta-analysis regardless of their quality.…”
Section: Meta-analysismentioning
confidence: 99%
“…A total of 15 studies with 2025 participants examined the relationship between ED and FMD. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] They all measured brachial FMD; however, the methods of FMD assessment were not universal among the studies. Seven of the 15 studies had the cuff placed on the forearm (including one which described the wrist), [28][29][30][31][32]37,39 while the others either had the cuff inflated over the arm 36,38,40,42 or did not specify.…”
Section: Erectile Dysfunction and Flow-mediated Dilationmentioning
confidence: 99%